Effect of cantilever length and framework alloy on the stress distribution of mandibular-cantilevered implant-supported prostheses - Jacques, Leticia Borges; Moura, Marcio Silva [UNESP]; Suedam, Valdey; Sousa, Edson Antonio Capello [UNESP]; Rubo, Jose Henrique (Wiley-Blackwell Publishing, Inc, 2009)
The purpose of this in vitro study was to analyze the stress distribution on components of a mandibular-cantilevered implant-supported prosthesis with frameworks cast in cobalt-chromium (Co-Cr) or palladium-silver (Pd-Ag) alloys, according to the cantilever length.Frameworks were fabricated on (Co-Cr) and (Pd-Ag) alloys and screwed into standard abutments positioned on a master-cast containing five implant replicas. Two linear strain gauges were fixed on the mesial and distal aspects of each abutment to capture deformation. A vertical static load of 100 N was applied to the cantilever arm at the distances of 10, 15, and 20 mm from the center of the distal abutment and the absolute values of specific deformation were recorded.Different patterns of abutment deformation were observed according to the framework alloy. The Co-Cr alloy framework resulted in higher levels of abutment deformation than the silver-palladium alloy framework. Abutment deformation was higher with longer cantilever extensions.Physical properties of the alloys used for framework interfere with abutment deformations patterns. Excessively long cantilever extensions must be avoided.To cite this article:Jacques LB, Moura MS, Suedam V, Souza EAC, Rubo JH. Effect of cantilever length and framework alloy on the stress distribution of mandibular-cantilevered implant-supported prostheses.Clin. Oral Impl. Res. 20, 2009; 737-741.doi: 10.1111/j.1600-0501.2009.01712.x.
Keywords: biomechanics; dental implants; mechanical stress; strain gauges